The effect of integrated lifestyle modification on quality of life and cost-effectiveness in atrial fibrillation ablation – results from the POP-AF RCT - Jasper Vermeer; Gijs van Steenbergen; Fabienne Vervaat; Sabine Grimm; Dennis van Veghel; Lukas Dekker (European Heart Journal - Quality of Care and Clinical Outcomes, 2026)
Abstract Objectives To evaluate the impact of an integrated lifestyle intervention on quality of life and cost-effectiveness in patients undergoing catheter ablation for atrial fibrillation (AF), compared with usual care. Methods The POP-AF trial randomized patients for their first AF ablation who had at least one modifiable lifestyle-related risk factor between lifestyle intervention and usual care. Quality of life was assessed throughout the trial using the Atrial Fibrillation Effect on Quality of Life (AFEQT) questionnaire. Treatment burden was evaluated using the Treatment Burden Questionnaire (TBQ). Health state was assessed using the EuroQol 5-Dimension (EQ-5D). Quality-adjusted life years (QALYs) were calculated from health states over time and used to calculate incremental cost-effectiveness ratio (ICER). Results A total of 145 patients participated (74% male; median age 62 years). At 3 months post-ablation, both groups demonstrated significant improvement in AFEQT (p<0.001), with higher scores in the intervention group (88.9 vs 80.6; p=0.026). At 12 months, this difference diminished due to continued improvement in the control group. Throughout the study, TBQ, EQ-5D and QALYs did not differ significantly between groups. The lifestyle intervention was associated with lower costs at the expense of a small reduction in QALYs, resulting in an ICER of €16,589 saved per QALY lost. Conclusions Both lifestyle intervention and usual care were associated with marked improvements in AF-specific quality of life following ablation. The lifestyle intervention reduced healthcare costs with minimal impact on health outcomes, supporting structured lifestyle modification as a cost-effective addition to pre-ablation AF care. Trial registration number: NCT05148338